(untitled) (Chemical Engineering Research Bulletin, 2026)
The creation of sustainable and environmentally friendly materials has become more important in order to address concerns about the depletion of nonrenewable resources and the negative environmental impact of traditional materials. In this study, a composite material made of glass fibre, banana fibre, and chicken feathers with varying fibre content percentages (1%, 2%, and 3%) was examined. The composite material was put through tensile, flexural, microhardness, and impact tests. An SEM was used to look at the sample’s surface and interior structure. FTIR analysis was performed to detect any contaminants in the sample. The impact of adding eggshell powder to the composite material to improve its qualities was investigated. It was found that the water absorption of the composite was reduced by 12%, and the tensile strength increased by 21% with the addition of eggshell powder. Furthermore, the flexural strength improved by 19%, enhancing the overall mechanical characteristics of the composite material. The addition of eggshell powder altered the interaction between the fibres and the matrix in SEM images. Furthermore, the composite material was subjected to soil exposure for a specific timeframe to evaluate its biodegradability over time. It was observed that integrating eggshell powder into composite materials has the potential to produce more ecologically friendly and sustainable products while reducing waste. This study emphasizes the potential of sustainable and environmentally friendly materials for decreasing environmental effects and ensuring long-term sustainability. Chemical Engineering Research Bulletin: 24 (Issue 1): 79-94